OUR EXPERIENCY WITH USING THE OMENTAL FLAP FOR THE TREATMENT OF GYNECOLOGIC JATROGENIC VESICOVAGINAL FISTULAS - Saidi, Skender; Stavridis, Sotir; Stojovska Jovanovska, Elizabeta; Ismaili, Bashkim; Dalipi, Adelina; Mojsova Mijovska, Maja (SHMSHM - AAMD, 2018)
Objective: To report our experience with using the omental flap for the treatment of gynecologic jatrogenic vesicovaginal fistulas (VVF). Material and methods: The study evaluated 14 patients who underwent VVS repair with transabdominal approach with omental flap between January 2010 and December 2013. The main causes of VVF in this study cohort were 9 (64.2%) for benign and 5 (35.8%) for malignant conditions. In all cases were used omental flap with sufficient length in delayed surgical repair (after 3 month of gynecologic surgery). Preoperatively the cystoscopi with colposcopy was done to identify the size, site, number of fistulas and relationship with ureteral orifices and sites of vagina. In addition CT urography or intravenous pyelograms were performed to exclude the ureterovaginal fistulas. The dorsal lithotomy position, with infraumbilical laparothomy approach and transvesical O’Connor technique in general anesthesia were used. Before resection of fistulous canal up to fresh and healthy tissue the intubation of ureteral orifices were performed. Further multilayer defect closure beginning from vagina, omental flap interposition, followed by bladder serosa and mucosa. Next 7 days bladder was drained with urinary catheter, cystostoma and ureter stents, which were pulled out one by one next 2 days. At 10th day, before catheter removal was performed cystogram. Results: Operative method is successful in 13 (93%) of patients. After one year follow up it’s no recurrence. The bladder capacity is sufficient. Conclusion: O’conore’s technique for repairing subtrigonal and supratrigonious vesicovaginal fistulas over 10 mm in wide, with the omentum interposition, is a method that promise a high percentage of success in the first repair.
Keywords: vesicovaginal fistula; O’Connor technique; omental flap